Brian's hunt - Paulsen, Gary. (New York : Wendy Lamb Books, 2003)
Two years after having survived a plane crash into the Canadian wilderness, a sixteen-year-old returns to the wild to befriend a wounded dog and hunt a rogue bear.
Keywords: Dogs -- Fiction; Hunting -- Fiction; Bears -- Fiction